On Shear Connection Design in Composite Beams - Jan Bujnak; Kazimierz Furtak; Jaroslav Odrobinak (Communications - Scientific letters of the University of Zilina, 2002)
The paper deals with a way of determining concrete pressure strength when calculating load carrying capacity of steel perfobond strip connectors. This type of strip connectors has been used in composite bridges only recently and no precise methods of calculating them have been worked out so far. The effect of axial forces on bearing capacity of classical stud shear connectors is also given in the paper as a result of research.